The use of crosshead displacement in determining fracture parameters: - Walters, C.L.; Voormeeren, L.O.; Janssen, M. (2013)
In determining the fracture toughness of a test specimen, standards currently require either locally-measured load-line displacements or clip gage displacements. In order to measure these parameters, secondary sensors generally need to be installed and calibrated, which often comes at a higher cost. As crosshead displacements are automatically measured in most modern material test machines, use of the crosshead measurements alone would be less expensive. Although much criticism exists on the accuracy of this approach in determining CTOD values, the method can still prove sufficiently accurate for many applications. The current paper aims to assess the magnitude of the errors that arise from using the crosshead displacement in fracture mechanics testing of steels with the Single Edge Notched Bending (SENB) specimen geometry. The results show that for steels with sufficiently large toughness, the use of the crosshead displacement to calculate J and convert to CTOD produces results within 10% of calculating the CTOD directly with conventional techniques.